Initial‐valued first‐order fuzzy differential equation in Bi‐level inventory model with fuzzy demand - Das, Barun; Mahapatra, Nirmal Kumar; Maiti, Manoranjan (Mathematical Modelling and Analysis, 2008)
In the present paper, two methods for the solution of an initial valued first ordered fuzzy differential equation are presented and applied in a fuzzy EOQ model. The constructed model is a bi‐level inventory problem involving wholesaler‐retailers‐customers. The wholesaler buys and sells the item instantaneously to several retailers. In the next level, the retailers sell the units to customers with a time dependent imprecise demand, which introduce the fuzzy nature in the differential equation. The selling price of the item is a step‐wise time dependent decreasing function. The fuzzy objectives are transformed into crisp one following fuzzy extension principle and centroid formula. The model is illustrated through Interactive Fuzzy Decision Making (IFDM) and Multi Objective Genetic Algorithm (MOGA) and the results from two methods are compared. First Published Online: 14 Oct 2010